Performance analysis of double CPV/TEG units in different arrangements coupled with water/air cooling channels - Selimefendigil, Fatih; Okulu, Damla; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
The extremely high temperatures reached by concentrated photovoltaic (CPV) panels have undesirable consequences on the performance of these systems. Different approaches are offered for thermal management of those systems. Concentrated photovoltaic/thermal (CPV/T) systems are utilized with thermoelectric generators (TEGs) in many studies. Thus, both a more advanced cooling performance and higher electrical power are achieved. In this study, the effects of different channel arrangements on CPV/T-TEG system are investigated by using two identical CPV-TEG units which are assembled on three different channel designs. Energy and exergy analysis of two CPV-TEG units which are combined in different arrangements are studied with appropriate single cooling channel design. Vertical arrangement (Model 1), inclined arrangement (Model 2) and horizontal arrangement (Model 3) of CPV/TEG units are taken into consideration while either air or water is used in the channels as the cooling medium. Different CPV/ TEG arrangements (Models 1,2 and 3) and cooling fluid inlet temperatures (between 15 degrees C to 35 degrees C) are considered for both air and water as the cooling fluid for a fixed value of Reynolds number of 1000. Galerkin weighted residual finite element method (FEM) is utilized as the solver while temperature distributions, PV and TEG electrical powers, energy and exergy efficiencies of water and air-based systems are analyzed for different arrangements and operating parameters of CPV/TEG units. Water-CPV/TTEGs has lower cell temperature and higher PV and TEG power than air-CPV/T-TEGs in each of the arrangements for both units. When highest PV powers are compared, water-Model 2 of B unit is 4.23 % higher as compared to air-Model 1 of unit A. The highest TEG power is achieved with Model 2A in both air- and waterbased dual CPV-TEG. TEG electrical power of water-Model 2A is 18.5 % higher than that of air-Model 2A. TEG efficiency for the water and air-based models are 1.664 % and 15.9 %, respectively. The water-Model 2B's PV cell temperature increases by 33.74 % and the air-Model 1A's increases by 25.7 % when the input temperature is increased from 15 degrees C to 35 degrees C. The highest total exergy efficiency is obtained with water in Model 2 and air in Model 3. The total exergy efficiency of the water-based Model 2 at the lowest inlet temperature is 2.8 % higher than that of air-based Model 3. Different channel arrangements and applied cooling fluids had an impact on the dual CPV-TEG. For future studies, the efficiency of both PV and TEG can be improved with optimum channel design by using shaped optimized algorithms and utilization of baffles in channels. In addition, the application of an innovative fluid instead of the conventional fluid in the channel system may enable the enhancement of these cooling system performances.
Keywords: Double CPV/TEG; Exergy analysis; Coolant; CFD; Cooling channel